Prevalence and factors associated with alcohol and other drug use among secondary school student leaders in Uganda, 2024 - Charity Mutesi; Byamah Mutamba; Kenneth Kalani; Richard Migisha; Emmanuel Mfitundinda; Emmanuel Okello Okiror; Joanita Nalwanga; Hannington Katumba; Patrick Kwizera; Lilian Bulage; Benon Kwesiga; Daniel Kadobera; et al. (Journal of Interventional Epidemiology and Public Health, 2026)
Introduction: Alcohol and other drug (AOD) use among adolescents is a growing public health concern, affecting their health, academic performance, and cognitive development. This study aimed to determine the prevalence, types, and factors associated with AOD use among secondary school student leaders in Uganda, 2024. Methods: We conducted a cross-sectional study among secondary school student leaders attending the 2024 annual prefects’ conference in Kampala. Participants were selected systematically from registration lists. Data were collected using self-administered questionnaires. Ever use was defined as lifetime AOD use, and current use as use within the past 30 days. Modified Poisson regression was used to identify factors associated with current AOD use. Results: Among the 569 participants, 70% (400) were male, 74% (423) were ≥18 years (median: 19 years, interquartile range: 17–20), and 58% (329) were in an advanced class level. Twenty-seven per cent (155/569) had ever used AOD, while 18% (103/569) reported current use. Alcohol was the most commonly used substance (55% of ever users, (86/155). Current use was mainly with friends [53% (55/103)] and at home [55% (57/103)]. Attending a private school (aPR=2.4, 95% CI=1.3–4.5) was associated with higher AOD use. Conclusion: Alcohol and other drug use among student leaders was high, with nearly one-fifth reporting current use. School-based prevention efforts should focus on strengthening oversight in private schools and enhancing parental engagement across all class levels.